Development of MIT App Inventor-Based Learning Media Using Project Based Learning Model on Molecular Gastronomy Material to Improve Students’s Learning Outcomes - Sabrina Sholihatus Sa'adah; Saptariana Saptariana (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Observations at SMK Widya Praja Ungaran revealed that every student has at least one Android smartphone used in daily activities, indicating an opportunity to utilize technology as a more interactive and independent learning medium. This study aims to: (1) develop MIT App Inventor-based learning media using the Project Based Learning Model on molecular gastronomy material; (2) determine the feasibility of the developed media; and (3) measure the improvement in student learning outcomes. The study employed the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The instrument validity test resulted in 36 valid items out of 45 items tested. The reliability test using Cronbach’s Alpha indicated a very high level of reliability. Feasibility was evaluated by material and media experts, resulting in scores of 94.6% and 100%, respectively—both categorized as Very Feasible. Learning outcome improvement was measured using N-gain analysis (Hake, 2002), yielding an average N-gain of 0.80 (80.1%)—categorized as High—indicating that the MIT App Inventor-based learning media has been proven feasible and capable of improving student learning outcomes on molecular gastronomy material.